Analisis Perubahan Penjualan dan Laba Terhadap Kinerja Keuangan pada PT. XYZ - Yeni Amelia (STIKes Ibnu Sina Ajibarang, 2023)
The purpose of this research is to find out the analysis of changes in sales, profits, and financial performance of PT. XYZ. Sales is one of the activities carried out by the company to maintain its business so that it can develop and compete with other companies so that it can easily obtain the profit or profit that the company wants. Profit is one indicator of a company's success in running its business. However, there are other indicators besides profit needed by the company to survive in the future. Financial performance is a description of the economic results that can be achieved by a company at a certain time through the company's activities.This study uses a descriptive quantitative analysis method and uses primary data in the form of sales reports, costs or expenses, and profit reports for 2018-2022. Changes in profit obtained a significant value of T of 0.000 less than 0.05, meaning that changes in profits partially affect the financial performance of PT. XYZ. This shows an increase in profit changes can affect the increase in the company's financial performance